SIMBOL-SIMBOL RELIGIUS DALAM SAKRAMEN DI GEREJA KATOLIK (SUATU ANALISIS SEMIOTIK) - Manusama, Yesika Magdalena; Rambing, Rosalina; Pamantung, Rina P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTSymbol is a sign which refer to an object. The religious symbols are representation of something that transcendental or occult and beyond the human thought. In this research the writer focus to kind of religious Symbols that exist in the celebration of sacrament that divided into seven types which is Baptism, Eucharist, Confirmation, Reconciliation, Marriage, Ordination, Anointing of the sick. The objective of this research is to identify, classify and analyze the meaning of symbols that exist in sacrament celebration. In collecting data, the writer focuses on identifying kinds of religious symbols based on Riches theory in Dillstone (2002) and then analyzes the meaning of those symbols by using Brodbeck’s theory in Sobur (2013).The method used in this research is Descriptive method. The result of this research is there are 47 religious symbols that found in Catholic Sacraments and all of those symbols have relation with God, nature, human and life reality.Key words: Semiotic, Religious symbols,Catholic Sacraments